A Validation System for the Complex Event Processing Directives of the ATLAS Shifter Assistant Tool. Issue 6 (December 2015) - Santos, A; Anders, G; Avolio, G; Kazarov, A; Miotto, G Lehmann; Soloviev, I
Abstract: Complex Event Processing (CEP) is a methodology that combines data from many sources in order to identify events or patterns that need particular attention. It has gained a lot of momentum in the computing world in the past few years and is used in ATLAS to continuously monitor the behaviour of the data acquisition system, to trigger corrective actions and to guide the experiment's operators. This technology is very powerful, if experts regularly insert and update their knowledge about the system's behaviour into the CEP engine. Nevertheless, writing or modifying CEP rules is not trivial since the used programming paradigm is quite different with respect to what developers are normally familiar with. In order to help experts verify that the rules work as expected, we have thus developed a complete testing and validation environment. This system consists of three main parts: the first is the data reader from existing storage of all relevant data streams that are produced during data taking, the second is a playback tool that allows to re-inject data of specific data taking sessions from the past into the CEP engine, and the third is a reporting tool that shows the output that the rules loaded into the engine would have produced in the live system. In this paper we describe the design and implementation of this validation system, highlight its strengths and shortcomings and indicate how such a system could be reused in similar projects.